2021
DOI: 10.1002/asi.24608
|View full text |Cite
|
Sign up to set email alerts
|

Struggling with digitized historical newspapers: Contextual barriers to information interaction in history research activities

Abstract: On account of the complexities related to the use of digitized newspapers, researchers may encounter barriers when interacting with the collections' content. Overcoming barriers that could influence their information interaction should enhance the accessibility and utility of the newspapers. Hence, the study examined the barriers faced in history‐research tasks involving interaction with digitized historical newspapers, with focus on the barriers' contexts and the related task‐based activities. The analysis em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Järvelin et al ., 2016; Bazzo et al ., 2020). As Kumpulainen and Late (2022) show empirically, noise in OCR quality disturbs researchers of historical newspaper collections both in the searching and selection phases of their research. In general, bad OCR quality concerns all users of the collections, although the quality may manifest differently to different user groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Järvelin et al ., 2016; Bazzo et al ., 2020). As Kumpulainen and Late (2022) show empirically, noise in OCR quality disturbs researchers of historical newspaper collections both in the searching and selection phases of their research. In general, bad OCR quality concerns all users of the collections, although the quality may manifest differently to different user groups.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, as recent empirical studies attest (e.g. Kumpulainen and Late, 2022; Late and Kumpulainen, 2021), the use of such collections is prone to be negatively affected by the noise present in digitized documents, caused by the errors made during the OCR process. However, the core question of how the variation in OCR quality affects the user has proved to be evasive.…”
Section: Introductionmentioning
confidence: 99%
“…Mayernik (2019) also considers metadata processes and products important in supporting day-to-day research tasks and meeting the requirements of funders, journals and data repositories. Kumpulainen and Late (2022) found that lacking or improper metadata was one obstacle to successful uses of newspaper contents in the history research domain.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, cultural information practices can be carried out through their online platforms or mobile applications even if they are not physically present at the cultural heritage institution. In recent years, many large-scale cultural heritage digitization projects have leveraged this virtual collaboration to carry out a range of impactful tasks (Davidson & Reid, 2022;Kumpulainen & Late, 2022;Owens, 2013).…”
Section: Co-creation Between Institutions and Undefined Crowdsmentioning
confidence: 99%
“…For example, Tencent, one of China's Internet giants, has launched the TANYUAN Project (https://tanyuan.qq.com/home) in recent years to digitize cultural heritage to help the VCC from different perspectives. Academic institutions can contribute to cultural heritage information practices by providing expertise and scientific research (Zhao et al, 2020), and many high-impact cultural heritage digitization projects have the support of academic institutions (Hu et al, 2018;Kumpulainen & Late, 2022;Liang et al, 2020;Price, 2016;Tedd, 2011). Finally, both traditional mass media and emerging social media are important channels to help publicize and promote information practices in the cultural heritage field (Sabharwal, 2021;Tedd, 2011).…”
Section: Core Actors Of Vccmentioning
confidence: 99%